Japanese Buddhist Canon Depicting Heavenly Sovereigns - Yu. L. Kuzhel; T. I. Breslavets (Ежегодник Япония, 2022)
In the Japanese Buddhist canon, the heavenly sovereigns belong to the fourth class of Buddhist deities — after the Buddhas, bodhisattvas, and light kings. They are the largest group. Sculptures are distinguished by the complexity of plastic forms, decorativeness, and expression. In Japanese iconography, the appearance of Buddhist characters was transformed according to ethnic requirements; their attributes, costumes, and poses changed. The heavenly sovereigns, with soft faces reminiscent of bodhisattvas, were endowed with formidable features in Japan; secular attire was changed to the attire of warriors. Other deities, initially considered warlike, acquired a peaceful appearance. Four heavenly sovereigns (shitennō) should be singled out as the most famous — Tamonten, Jikokuten, Zōchōten, Kōmokuten. They hold weapons in their hands. For Kōmokuten, in his fight against ignorance, the word serves as a weapon, and he holds a scroll-sutra and a brush. In addition to them, Bonten, Taishakuten, Bishamonten became recognized. They have great physical and spiritual strength and appear in majestic poses. Bishamonten acts as a warrior-protector but is also a deity who bestows mercy on everyone. The warrior Benzaiten took on the traits of femininity. Kichijōten is known as the goddess of wealth and happiness. The cohort of heavenly sovereigns belong to the guardian deities of Buddhist law — Shūkongōjin and Kongōrikishi. They are akin to guards located in the niches of temple gates. Sacred sculptures demonstrate the martial spirit with a powerful physique, facial expressions, hand gestures, military armor. Initially static, the sculptures acquired expressiveness of movement due to the position of arms and legs. The article considers the most artistically significant sculptures to trace the process of improving the stylistic means of sculpting Japanese-Buddhist images, to reveal the features of grotesque works, and to expand knowledge about Buddhist temple sculpture.